U-Pb geochronology of the Cape Smith Belt and Sugluk block, northern Quebec - Parrish, Randall (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1989)
Summary The Cape Smith Belt is a multiply-deformed thrust belt containing metamorphosed basaltic volcanic, mafic intrusive, and sedimentary rocks. It lies south of the Kovikanti form and the Sugluk block; together, these constitute the Ungava segment of theTrans-Hudson Orogen. U-Pb dating of representative units reveals that Archean rocks of the Superior craton which underlie the belt are ca. 2780-2880 Ma old, and that theoldest rocks in the belt proper are those of the Purtuniq ophiolite at 1998 ± 2 Ma. The belt evolved between ca. 2000 Ma (oceanic crust generation) and about 1830 Ma, the age of the later part of the belt's south-directed structural translation and subsequent thick-skinned deformation. The Po-vungnituk Group (the structurally lowest assemblage of sedimentary and volcanic rocks) was deposited ca. 1960 Ma, and being younger than the ophiolite, cannot be the rift assemblage which led to creation of oceanic crust of the Purtuniq ophiolite. Ages of intrusions and sedimentary rocks within the Sugluk block are as young as 1830 Ma,and they were metamorphosed and deformed at granulite faciès at 1830-1820 Ma, prior to a period of slow cooling.